A Comparative Study on Bioactivities of Aqueous Extracts from Various Parts of Moringa Oleifera - Annissa Annissa; Hanif Amrulloh; Hamed Kioumarsi (Bioactivities, 2025)
Moringa oleifera (M. oleifera) is widely recognized as a rich source of natural antioxidants; however, systematic comparisons of the phytochemical composition and biological activities of aqueous extracts obtained from different plant organs remain limited. This study aimed to comparatively evaluate the phytochemical profiles, antioxidant capacity, antibacterial activity, and antifungal activity of aqueous extracts prepared from the leaves, twigs, stem bark, and wood of M. oleifera. Qualitative phytochemical screening, determination of total phenolic and total flavonoid contents, Fourier-transform infrared spectroscopy, 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay, and resazurin-based microdilution assays against representative bacterial and fungal pathogens were performed. Leaf and twig extracts exhibited the greatest phytochemical diversity, whereas the wood extract showed the simplest composition. The leaf extract contained the highest total phenolic content (683.95 ± 16.74 μg gallic acid equivalents mL⁻¹) and total flavonoid content (514.08 ± 26.12 μg catechin equivalents mL⁻¹), followed by the twig, bark, and wood extracts. Consistently, the leaf extract demonstrated the strongest antioxidant activity, with 64.60 ± 0.69% radical scavenging activity, approaching that of the reference antioxidant (71.72 ± 0.56%). Fourier-transform infrared spectroscopy confirmed the presence of hydroxyl, carbonyl, aromatic, and ether functional groups associated with phenolic and flavonoid compounds, particularly in leaf and twig extracts. Antibacterial and antifungal activities followed the same overall trend, with leaf extracts exhibiting the greatest inhibitory effects, followed by twig, bark, and wood extracts. These findings demonstrate that the distribution of bioactive phytochemicals is strongly organ-dependent and closely associated with antioxidant and antimicrobial activities. The study identifies M. oleifera leaves as the most promising source of water-extractable antioxidant compounds and supports their potential application in the development of sustainable functional foods, nutraceuticals, and phytopharmaceutical products.